An interactive storytelling game for mobile devices for children's stress management - Iolie Nicolaidou; Tozzi, Federica; Kindynis, Philippos; Panagiotou, Marinos; Antoniades, Athos (My University, 2017)
Around 40% of children experience subclinical anxiety and the median onset age for anxiety disorders is 6 years-old. Informal-learning, stress prevention interventions, accessible on children's mobile devices, could be one way to address this problem. Most existing mobile applications are adapted from adult-targeted approaches for anxiety treatment. There are limited game-based apps available for helping children identify and self-manage stress. To address this gap, an interactive storytelling serious game for mobile devices was designed for 5-11 year-olds, to help children identify body signs of stress and overcome stress through relaxation techniques. It was developed by Stremble Ventures LTD (www.stremble.com) and it is offered at www.kidsstressrelief.com currently on Android. The aim of this study was to evaluate the game's acceptability and usability, focusing on design characteristics with wide applicability in future prevention interventions in children. The research questions are: a) How do children between 5-11 years-old perceive stress signs and relaxation techniques presented through an interactive storytelling game? b) What are children's perceptions of the game's usability? Participants were eleven children (5-11 years old). Convenience sampling was used, reaching families with different socioeconomic background. Data sources included: a) a researcher-led usability evaluation protocol guiding children's videotaped interaction with the game, b) the System Usability Scale (SUS), and c) automatically-collected data capturing children's interaction with the app. Preliminary findings show promising results for the game's acceptability for identifying stress signs and practicing relaxation techniques, especially for children older than seven. Preliminary findings were also satisfactory with respect to the game's usability (raw average SUS scores=74.77). Instructional and design implications, of interest to developers of psychology-based apps, are drawn.
Keywords: Children; Interactive story-telling; Kids stress relief; Prevention intervention; Serious game (app); Stress management